BIOREMEDIATION OF TEXTILE EFFLUENT BY INDIGENOUS BACTERIAL CONSORTIA AND ITS EFFECTS ON Zea mays L. CV C1415 - R. Mahmood; F. Sharif; S. Ali; M. U. Hayyat (Journal of Animal and Plant Sciences, 2013)
Bacterial consortia BMP1 (containing six isolates), BMP2 (three isolates) and BBP (three isolates) were isolated fromtextile affected soil, sludge and effluent of Hudiara drain in vicinity of Nishat Mills Limited 5Km Off - 22Km Ferozepur Road Lahore, Pakistan. These consortia were capable of degrading red, green, black and yellow dyes and were resistant to heavy metals (Cu, Cd, Cr, Ni, Mn & Pb). They were equally beneficial for the reduction of other pollution parameters like colour, pH, EC, nitrogen, phosphorus, chloride, COD, BOD, TDS and TSS from textile effluents. The physicochemical characterization of textile effluents was carried out before and after treatment by consortia to sort out most efficient consortium. The results indicated that the consortium BMP1 showed maximum reduction of EC (52.98%), pH (11.85%), nitrogen (79.02%), phosphorus (68.78%), chloride (46.42%), BOD (59.49%), COD (61.35%), TDS (44.93%) and TSS (52.58%). It was also helful in reduction of heavy metals such as Cu (92.3%), Cd (89.46%), Cr (83.52%), Ni (80.7%), Mn (88.3%) and Pb (93.5%). Effect of untreated and treated textile effluents was investigated on maize (Zea mays L. CV C1415) and it was observed that effluent treated by consortium BMP1 was not toxic to maize crop in comparison to untreated effluent. The current study revealed that utilization of bacterial consortium for textile effluent treatment could be an effective method.
Keywords: Textile effluent; bioremediation; maize; bacterial consortia